The Association Between Patient Satisfaction and Patient-Reported Health Outcomes. (September 2019) - Chen, Qinyu; Beal, Eliza W; Okunrintemi, Victor; Cerier, Emily; Paredes, Anghela; Sun, Steven; Olsen, Griffin; Pawlik, Timothy M
Objective: Although patient satisfaction is increasingly used to rate hospitals, it is unclear how patient satisfaction is associated with health outcomes. We sought to define the relationship of self-reported patient satisfaction and health outcomes. Design: Retrospective cross-sectional analysis using regression analyses and generalized linear modeling. Setting: Utilizing the Medical Expenditure Panel Survey Database (2010-2014), patients who had responses to survey questions related to satisfaction were identified. Participants: Among the 9166 patients, representing 106 million patients, satisfaction was rated as optimal (28.2%), average (61.1%), and poor (10.7%).Main Outcome Measures: We sought to define the relationship of self-reported patient satisfaction and health outcomes. Results: Patients who were younger, male, black/African American, with Medicaid insurance, as well as patients with lower socioeconomic status were more likely to report poor satisfaction (all P < .001). In the adjusted model, physical health score was not associated with an increased odds of poor satisfaction (1.42 95% confidence interval [CI]: 0.88-2.28); however, patients with a poor mental health score or ≥2 emergency department visits were more likely to report poor overall satisfaction (3.91, 95% CI: 2.34-6.5; 2.24, 95% CI: 1.48-3.38, respectively). Conclusion: Poor satisfaction was associated with certain unmodifiable patient-level characteristics, as well as mental health scores. These data suggest that patient satisfaction is a complex metric that can be affected by more than provider performance.